Effect of Declination and Solar Radiation Intensity on Weather Parameters in 2020-2023 in Padang City - Juliana Dekriani; Letmi Dwiridal; Harman Amir; Zulhendra Zulhendra (BULETIN FISIKA, 2025)
Padang City is an area that often has an extreme climate so that it is at risk of potential natural disasters that are difficult to predict. This study aims to determine the effect of declination and solar radiation intensity on weather parameters that occur in Padang City in 2020- 2023. The data used are solar declination data, solar radiation intensity and weather parameter data (rainfall intensity, air temperature and air humidity). The research conducted is quantitative research using secondary data obtained from the Class II Minangkabau Meteorological Station Padang Pariaman. Modeling is done using a surfer to get the contours of declination, solar radiation intensity and weather parameters. The result obtained are obtained are that solar declination reaches a peak point on June 21 with 23.44o LU and on December 21 with 23.44o LS. The higher the solar declination North Latitude Direction the Intensity of solar radiation and air temperature that occurs is higher but not in the solar declination of south latitude direction. The higher the intensity of solar radiation, the lower air humidity and rainfall intensity. December 30, 2022 solar declination is 23.13o LS, solar radiation intensity is 96.62 J/m2s2, air temperature is, temperature 24 o C, air humidity is 89% and rainfall intensity is 46.5 mm. While on June 24, 2021 the declination of the sun is 23.4o LU, the intensity of solar radiation is 155.11 J/m2s2, the air temperature is 27.3o C, the air humidity is 77% and the rainfall is 0 mm.